Using Interactive Multimedia to Stimulate Early Childhood Students’ Speaking Skills: A Systematic Review - Yeni Lestari, Ni Gusti Ayu Made; Boeriswati, Endry; Dhieni, Nurbiana (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Interactive multimedia is currently a significant topic in terms of learning speaking skills. This study aims to describe the use of interactive multimedia in stimulating early childhood speaking skills based on a literature review that has been conducted. The study method used in this literature study is the PRISMA (preferred reporting items for systematic reviews and meta-analyses) method. Data was obtained from the Scopus and Google Scholar databases using scientific articles from reputable international journals with the Scopus Q1–Q4 index. Article searches using the title and keywords “Interactive Multimedia,” “Multimedia,” “Interactive Multimedia in Early Childhood,” or “Speaking Skills” are limited to the last ten years, starting from 2013–2023. The findings showed that the articles in the source database were 10.982 articles, and the final selected papers left 40 articles for review. The results of the study found that: a) the use of interactive multimedia in early childhood learning is dominated by Android-based interactive multimedia (50%), video (30%), and animation (20%); b) the use of interactive multimedia in stimulating early childhood speaking skills is dominated by android media (45%), video (40%), and animation (15%); c) the challenges faced when using interactive multimedia in early childhood learning are limited infrastructure and resources, and not all schools have adequate facilities for the use of technology-based learning media and a lack of teacher creativity. The contribution of this research can provide insight into the use of interactive multimedia to stimulate early childhood speaking skills effectively and efficiently. Thus, the use of interactive multimedia can be a research target in selecting interactive multimedia that is appropriate and effective for stimulating students’ speaking skills at all levels of education and on different research topics.